PEMAHAMAN AKUN DAN BASIS PENCATATAN AKUNTANSI DENGAN ALAT PERAGA EDUKATIF BAGI SISWA SMA KRISTOFORUS I - Imelda, Elsa; Michelle Tjen; Stella Maris (Jurnal Serina Abdimas, 2024)
Many people say that accounting knowledge will disappear in the era of digitalization because accountants' jobs can be replaced by information technology, especially considering that artificial intelligence is developing rapidly in the current era. This is the first problem of the decline in high school students' interest in the field of accounting. In fact, the accounting profession will not disappear but will experience quite a significant transformation. Accountants will focus more on middle to upper management levels for strategic roles and business development. This requires a good understanding of basic accounting. Meanwhile, Accounting lessons at high school level are currently only an option in the Kurikulum Merdeka. This causes students not to understand the importance of accounting and becomes the second problem for the decline in high school students' interest in accounting. For this reason, the Untar PKM team developed an accounting laboratory at Kristoforus I High School, Jakarta. One of the topics that is fundamental to understanding accounting is understanding accounts and the basis for accounting records. Account classification is divided into three, namely assets, liabilities and equity. Students must first understand the classification of these accounts before continuing accounting recording activities. Then the recording bases explained are the cash basis and the accrual basis. The PKM team explains why the accrual basis is used in accounting records. The PKM team developed teaching techniques using educational tools to make it easier for students to understand the material ABSTRAK Banyak kalangan yang mengatakan ilmu Akuntansi akan hilang di era digitalisasi karena pekerjaan akuntan sudah dapat diganti oleh teknologi informasi, apalagi mengingat kecerdasan buatan (Artificial Intelligence) yang berkembang pesat di era saat ini. Hal ini menjadi permasalahan pertama turunnya minat siswa SMA terhadap bidang akuntansi. Sebenarnya profesi akuntan tidak akan hilang tetapi mengalami transformasi yang cukup signifikan. Akuntan akan lebih berfokus di level manajemen menengah ke atas untuk peran strategis dan pengembangan usaha. Untuk itu dibutuhkan pemahaman akuntansi dasar yang baik. Sedangkan, pelajaran akuntansi di level SMA saat ini hanya menjadi opsi di kurikulum merdeka. Hal ini menyebabkan siswa tidak memahami pentingnya akuntansi dan menjadi permasalahan kedua bagi penurunan minat siswa SMA terhadap bidang akuntansi. Oleh sebab itu, tim PKM Untar mengembangkan laboratorium akuntansi di SMA Kristoforus I Jakarta. Salah satu topik yang menjadi fundamental bagi pemahaman Akuntansi adalah pemahaman akun dan basis pencatatan akuntansi. Penggolongan akun dibagi menjadi tiga, yaitu asset, liabilitas dan ekuitas. Siswa harus terlebih dahulu memahami penggolongan akun ini sebelum melanjutkan kegiatan pencatatan akuntansi. Kemudian basis pencatatan yang diterangkan adalah basis kas dan basis akrual. Tim PKM menjelaskan mengapa basis akrual yang dipakai dalam pencatatan akuntansi. Tim PKM mengembangkan teknik ajar dengan alat peraga edukatif untuk memudahkan siswa memahami materi.